Increasing Advance Care Planning Using a Surgical Optimization Program for Older Adults. - Kata, Anna; Sudore, Rebecca; Finlayson, Emily; Broering, Jeanette M.; Ngo, Sarah; Tang, Victoria L. (Journal of the American Geriatrics Society, 2018)
Objectives: To describe an innovative model of care, the Surgery Wellness Program (SWP), that uses a multidisciplinary team to develop and implement preoperative care plans for older adults, and its effect on engagement in advance care planning (ACP). Design: Retrospective analysis of clinical demonstration project. Setting: Preoperative optimization program for older adults undergoing surgery at a 796‐bed academic tertiary hospital. Participants: Older adults (N=131) who participated in the SWP from February 2015 to August 2017. Intervention: All SWP participants met with a geriatrician who engaged them in a semistructured ACP discussion. Trained medical and nurse practitioner students were used as health coaches who contacted participants regularly to address and document ACP. Measurements: Self‐report of ACP engagement before and after participation in the SWP was determined using SWP geriatrician and health coach progress notes. Medical records were examined for scanned documentation. Feasibility data on number of health coach calls were collected. Results: After completion of the program, the proportion of participants with a designated surrogate increased from 67% to 78% (p<.001), completed advance directive (AD) from 51% to 72% (p<.001), and an AD scanned into the medical record from 14% to 60% (p<.001). Participants who underwent surgery received a median of 4 health coaching calls over a median of 27 days between their clinic visit and surgery. Case examples are presented to highlight how the SWP attends to the many components of the ACP process. Conclusion: Preoperative optimization programs provide a unique opportunity to engage older adults in ACP. See related editorial by Jason Johanning